2022
DOI: 10.2147/ijgm.s387066
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Community Pharmacists’ Knowledge and Attitudes Toward Pain and Pain Management in Saudi Arabia

Abstract: Background Pain is a global health issue that affects an individual’s quality of life. Its alleviation and management will enhance patients’ experience. Community pharmacists can help manage pain severity through their valuable roles in medical teams and by managing the consequences of pain. Objective This study aimed to evaluate community pharmacists’ knowledge and attitudes toward pain and pain management in Saudi Arabia. Methods A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…18 Not only, pharmacists, but also physicians and nurses possess insufficient knowledge of pain and pain medication which urgently requires the need for more training and education on this burning issue. 22 This study revealed that more than three-fifths (61%) of the community pharmacists working in Bahir Dar City had less stigmatizing behavior toward opioid use problems. This implies that a significant number of pharmacists (around two-fifths) had stigmatizing behavior for opioid use and opioid use problems.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…18 Not only, pharmacists, but also physicians and nurses possess insufficient knowledge of pain and pain medication which urgently requires the need for more training and education on this burning issue. 22 This study revealed that more than three-fifths (61%) of the community pharmacists working in Bahir Dar City had less stigmatizing behavior toward opioid use problems. This implies that a significant number of pharmacists (around two-fifths) had stigmatizing behavior for opioid use and opioid use problems.…”
mentioning
confidence: 76%
“…31 Similarly, a study conducted in Saudi Arabia also revealed the positive role of experience on the overall knowledge and attitude towards pain management. 22 This difference might be due to the higher exposure time in the pharmacy setting, which enhances patient handling, as it is part of the patient care process.…”
Section: Dovepressmentioning
confidence: 99%
“…Community pharmacies are pivotal in delivering over-the-counter analgesics, as they offer a convenient avenue for individuals seeking pain relief. 8 The data highlights the significant contribution of community pharmacies in providing patient education and counseling on the proper use of analgesics. Previous study by Murphy et al, 20 stated that pharmacists must engage and guide patients actively, offering essential information on appropriate dosages, potential side effects, and necessary precautions when obtaining analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…6 Evaluating knowledge regarding potential adverse effects, appropriate dosages, contraindications, and potential drug interactions associated with analgesic use is of utmost importance. 7,8 The use of analgesics is also influenced by attitudes toward pain management and the tendency toward self-medication as an alternative to seeking medical advice. 4,[6][7][8] Pain reporting tends to be more common among women, older individuals, and those with lower socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation